Comparison of Oral Ivermectin and Permethrin 1% Shampoo in the Treatment of Pediculosis Capitis - Mehvish Afridi, Sara Inayat, Zaib ., Saifullah Kakar, Anila Panezai, Sehrish Ghani (Journal of Rawalpindi Medical College, 2021)
Objective: To compare the efficacy of Oral Ivermectin with Permethrin 1% Shampoo in the treatment of Pediculosis Capitis Study Design: Randomized controlled trial Setting & Study duration: This study was conducted at the Department of Dermatology, Bolan Medical College/ Sandeman Provincial Hospital, Quetta from December 24, 2016 to June 23, 2017 (6 months) Materials and Methods: All children of either gender having age 5 and above weight more than 15 kg presented with head-lice infestation confirmed by combing the wet hair with a fine-toothed detection comb were enrolled. All patients were randomly allocated into two groups. Patients in group A received oral Ivermectin in dose of 200mcg/kg while patients in group B received application of 1% Permethrin Shampoo. They were called after one week and they received second dose of oral Ivermectin in same dose of 200mcg/kg and application of Permethrin 1% Shampoo and re-evaluated after one week. Treatment was considered effective by absence of live lice by day 15 of treatment. Data was analyzed in SPSS version 17.Mean age of the patient in the sample was calculated. Male to female ratio was determined in the sample. In both the groups, frequency of patients having no live louse in the head on 15th day was calculated. The frequency in both groups was compared by applying chi square test keeping p-value≤ 0.05. Results: Majority of the patients presented were females in both group, i.e. 20 (66.7%) and 23 (76.7%) respectively. Insignificant difference was observed in the mean age in between group (p- value 0.482). Efficacy was found significantly higher in oral Ivermectin group 26 (86.7%) as compared to 1% Permethrin Shampoo. (p-value <0.001). Conclusion: The efficacy of oral Ivermectin group was considerably higher as compared to 1% Permethrin Shampoo in our cohort.